2000
DOI: 10.1034/j.1600-0501.2000.011004334.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological observations on biopsies harvested following sinus floor elevation using a bioactive glass material of narrow size range

Abstract: We evaluated the bone augmenting capacity of bioactive glass particles, size range 300-355 microns (BG-particles), in human sinus floor elevations using histomorphometrical methods. A total of 10 patients underwent bilateral grafting, using a 1:1 mixture of autogenous bone particles (from iliac crest) and BG-particles at one side (experimental side), and bone particles only at the other side (control side, split mouth design). A total of 72 bone biopsies were taken at the time of fixture installation; that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
1
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(184 citation statements)
references
References 21 publications
14
152
1
14
Order By: Relevance
“…Authors who did not describe randomization clearly were contacted via e-mail for additional information. When a proper randomization procedure was applied, these studies were added to the results 1,11,21,28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors who did not describe randomization clearly were contacted via e-mail for additional information. When a proper randomization procedure was applied, these studies were added to the results 1,11,21,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding bioactive glass TADJOEDIN et al 28 showed that augmentation with autogenous bone had resulted in a significantly higher bone fraction (42%) than treatment with bioactive glass (35%) 4 and 5 months after sinus floor elevation. TURUNEN et al 35 presented comparable results for both groups after 4 months of healing.…”
Section: Histomorphometric Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before preparation of the implant bed to install dental implants, a biopsy of the reconstructed area can be easily taken, which implicates no extra burden for the patient. 28,29 Moreover, all surgical procedures, except the extraoral grafting procedure, can be performed under local anesthesia. The selection of a donor site is often made on considerations driven by the quantity needed for the individual case.…”
Section: Discussionmentioning
confidence: 99%